Character Education in the Qur'an - Abdillah, Abdillah; Ihwan Amalih; Ghozi Mubarok (Penerbit Hellow Pustaka, 2025)
Character education is one of the important issues in the world of education, especially in the context of moral and ethical formation. In the Qur'an, character education receives significant attention, providing comprehensive guidance for forming a noble personality. The verses of the Qur'an teach values ​​such as honesty, discipline, responsibility, and empathy, which are essential in everyday life. Character education not only targets cognitive aspects, but also emotional and spiritual aspects. This study aims to explore how the concept of character education is explained in the Qur'an. Through an in-depth study of certain verses, it was found that the Qur'an provides a solid foundation for the development of individual morality. Character education in the Qur'an includes important aspects such as patience, gratitude, and trustworthiness, which form personal integrity and harmonious social relationships. This article also identifies the main problems in the implementation of character education based on the values ​​of the Qur'an, as well as the solutions offered by the Qur'an itself. Using qualitative methods and a thematic interpretation approach, this article examines relevant Qur'anic verses and suggests implementation steps that can be applied in the context of modern education.